Fetomaternal Outcomes in Women with Cervical Cerclage Experience in Tertiary Care Hospital - Mahsud, Huma; Akhtar, Naheed; Aman, Zeenat; Bibi, Basanara (Indus Journal of Bioscience Research, 2025)
Background: Cervical insufficiency is a significant cause of preterm delivery and spontaneous abortion in high-risk pregnancies. Cervical cerclage, a procedure to prevent premature cervical dilation, is commonly employed in such cases. However, its effectiveness in different demographic groups remains under debate. Objective: To determine the fetomaternal outcomes in women with cervical cerclage. Study Design: Descriptive observational study. Duration and Place of Study: The study was conducted at the Department of Obstetrics and Gynaecology, Khyber Teaching Hospital (KTH), Peshawar, from May 2023 to November 2023. Methodology: A total of 166 women aged 18-40 years, with a singleton pregnancy, gestational age ≤ 28 weeks, and diagnosed with cervical insufficiency, were enrolled. Cervical cerclage was performed under spinal anesthesia using McDonald technique. Results: The mean age of participants was 29.42 ± 5.69 years, with a mean gestational age of 21.86 ± 3.61 weeks. Spontaneous abortion occurred in 11.4% of cases, while 13.9% experienced preterm delivery. No significant associations were found between age, gestational age, or parity and the outcomes of spontaneous abortion or preterm delivery (p-value > 0.05). Conclusion: Cervical cerclage is an effective procedure in improving pregnancy outcomes for women with cervical insufficiency, though it does not eliminate the risk of spontaneous abortion or preterm delivery.